Effects of aflatoxin B1, fumonisin B1 and their mixture on the aryl hydrocarbon receptor and cytochrome P450 1A induction. (January 2015) - Mary, Verónica S.; Valdehita, Ana; Navas, José M.; Rubinstein, Héctor R.; Fernández-Cruz, María L.
Highlights: AFB1 induced Cyp1A and Ahr, but FB1 only raised slightly Cyp1A, in H4IIE cells. AFB1 and FB1, induced overexpression of the cyp1A and ahr genes, in spleen cells. Response potency was higher for the AFB1 –FB1 mixture, than for individual toxins. Results suggest Ahr pathway activation as a toxicity mechanism for AFB1 and FB1 . This study highlights that FB1 may increase bioactivation and toxicity of AFB1 . Abstract: Aflatoxin B1 (AFB1 ) and fumonisin B1 (FB1 ) are mycotoxins widely found as cereal contaminants and their co-occurrence in corn has been associated with a high incidence of liver cancer. Both toxins are immunotoxic, with AFB1 being a procarcinogen, and its bioactivation through specific cytochrome P450 (Cyp) enzymes, such as Cyp1A, being a requirement for hepatocarcinogenic and toxic activities. This study evaluated the effects of these mycotoxins, alone or combined, on activation and expression of Cyp1A and its transcription factor aryl hydrocarbon receptor (Ahr) in hepatoma cell line H4IIE and spleen mononuclear cells of rats. The results demonstrate that in H4IIE cells, AFB1 induced an increase in Cyp1A activity and cyp1A transcription, associated with an enhanced Ahr activity, which suggests that this toxin can act as an Ahr agonist. Moreover, FB1 caused a small rise in Cyp1A activity and cyp1A expression. Similarly in spleen cells, AFB1 and FB1 induced overexpression of cyp1A and ahr genes. This work shows that the response potency was significantly higher for the mixture, indicating the existence of an interaction between both toxins. This study proposes the Ahr pathway activation as a toxicity mechanism of AFB1 and FB1, and highlights that FB1 may increase AFB1 bioactivation.